Chemical composition of essential oil of the Litsea cambodiana Lecomte and Litsea salmonea A. Chev. from Bach Ma national park - Son, Le Cong; Huyen, Duong Duc; Thang, Tran Dinh; Dai, Do Ngoc (Academia Journal of Biology, 2013)
The essential oil of Litsea cambodiana and Litsea salmonea collected from Bachma National Park in July 2012 was isolated by the steam distillation. By using capillary GC and GC/MS methods the oil yield of two plant species was 0.30%, 0.23%, respectively. Fourty one components have been identified that accounts more than 98.71% of the oil from leaf of Litsea cambodiana. The major constituents of this oil were β-caryophyllene (28.36%), camphene (17.10%) and bicyclogermacrene (12.26%). Thirty three components were identified in stems oil of Litsea salmonea, which presented about 84.62% of the total composition of the oil. The major constituents of the essential oil were cis methyl isoeugenol (26.27%), (E)-nerolidol (11.60%), 3-methyl-1-phenyloxidole (8.57%) and (Z)- 9-octadecenamide (7.46%).